Clustering, Agency Costs and Operating Efficiency: Evidence from Nursing Home Chains - Lu, Susan F.; Wedig, Gerard J. (Management Science, 2013)
Models of horizontal integration typically describe a trade-off between multiunit efficiencies and managerial agency costs. In extreme cases where managers cannot be incented contractually, private ownership is thought to be the primary organizational substitute. In this paper we explore geographic clustering as an alternative strategy for controlling managerial agency costs within the chain form of organization. Clustering may facilitate scale efficiencies in both monitoring and supervision, resulting in reduced agency costs and improved application of the chain's business model. We test this hypothesis in the nursing home industry, which is characterized by managerial contract costs resulting from multitask models of production. We find that clustered nursing homes achieve higher quality, conditional on labor inputs and patient characteristics. The clustering effect is concentrated on reductions in minor/potential harm violations, which are difficult to observe without close monitoring. Several proxies for local organizational experience (“local learning”) cannot account for our findings, which are robust to a variety of alternative clustering definitions and competing explanations based on gaming behavior. Further tests indicate that chains endogenously pursue clustering, presumably to realize the benefits of improved quality outcomes. This paper was accepted by Bruno Cassiman, business strategy.